THEMATIC PROGRESSION AS A MODEL USED TO KEEP COHESION IN WRITING AN EXPOSITION TEXT - Rusdi Noor Rosa (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
This paper is aimed at modeling how thematic progression is used to keep cohesion of the text, especially the exposition text. This paper uses two expositions texts written by the students as the meadia to demonstrate the application of thematic progression in keeping cohesion of the texts. Then, the two texts that have been analyzed are presented to show how thematic progression can work to make the text cohesive. This paper concludes that the cohesion of the text can be improved by using thematic progression.